Class Room Action Research in English Language Learning - Rasuan, Zulfikri Betyar (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Research activities is common for a lecturer because it is a compoulsary term. Research in English Language or English learning is a scientific activity that aims at investigating the rules that work in the process of English learning. Research activities in English learning cover four steps: observing, describing, analyzing, and explaining. The way of each step is done depends on the nature of the data and the objective of the research. Classroom Action Research (CAR) for English Learning aims at developing a certain instructional strategy to solve practical instructional problems in English classrooms. Each English learner is basically able to learn English provided that he or she is given the appropriate help as each learner has his or her own style and strategy of learning. CAR for English Learning aims at discovering learning-teaching strategies that match learners’ style and strategies in learning English. CAR is done in several cyles each of which is repeated in the following cycle if the result is not satisfactory yet with the better revised lesson plan. Each cycle begins with lesson planning, implementing the plan, observing the implementation, and reflecing or evaluating the process and the result of the implementation. The result of the reflection determines the following cycle.